2008
DOI: 10.1007/s11071-008-9336-4
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear response and nonsmooth bifurcations of an unbalanced machine-tool spindle-bearing system

Abstract: In this effort, a six-degree-of-freedom (DOF) model is presented for the study of a machinetool spindle-bearing system. The dynamics of machine-tool spindle system supported by ball bearings can be described by a set of second order nonlinear differential equations with piecewise stiffness and damping due to the bearing clearance. To investigate the effect of bearing clearance, bifurcations and routes to chaos of this nonsmooth system, numerical simulation is carried out. Numerical results show when the inner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…With the increase of the frequency ratio, there are three possible routes to chaos in the spindle-bearing system: (1) through a period doubling bifurcation, (2) through a tori doubling process, and (3) through a grazing bifurcation [19]. These results enrich our understanding on the dynamics of the spindle-bearing system and are of great significance to the design and fault diagnosis for the spindle-bearing system.…”
Section: Route To Chaos Through Period-doubling Processmentioning
confidence: 82%
See 1 more Smart Citation
“…With the increase of the frequency ratio, there are three possible routes to chaos in the spindle-bearing system: (1) through a period doubling bifurcation, (2) through a tori doubling process, and (3) through a grazing bifurcation [19]. These results enrich our understanding on the dynamics of the spindle-bearing system and are of great significance to the design and fault diagnosis for the spindle-bearing system.…”
Section: Route To Chaos Through Period-doubling Processmentioning
confidence: 82%
“…(19) into (16), expanding F in a Taylor series about the nominal periodic solution X * , and retaining the linear terms of the perturbation X, the resulting system of linear time-varying coefficient differential equations is given,…”
Section: Floquet Multipliersmentioning
confidence: 99%
“…Sopanen and Mikkola proposed a dynamic model of a ball bearing-rotor system with six degrees of freedom to study the effects of the bearing clearance on the natural frequencies and the vibration responses of the system [15,16]. Based on it, Gao found that appropriate negative internal clearance helps to reduce the vibration responses of the spindle and improve the stability of the system [17,18]. Bearing preload could keep the bearing in a negative internal clearance state by eliminating the clearance, but too large preload will produce much frictional heat, leading to the rise of temperature and the decline of bearing life [19].…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al. 25 studied the grazing contacts between bearing races and balls on the dynamic responses of a rotor-ball bearing system. Numerical results showed that when the ball-race contact speed is low, grazing bifurcation occurs.…”
Section: Introductionmentioning
confidence: 99%